Relative density concept is not a reliable criterion - Hamidi, Babak; Varaksin, S.; Nikraz, Hamid (ICE Publishing, 2013)
Many years ago, a new concept called relative density was developed with the intention of appropriately defining the looseness and denseness of sand or sand–gravel soils in a meaningful way. Soon after, relative density found its way into ground improvement as an acceptance criterion by engineers who were more familiar with the construction of engineered backfilling rather than thick mass treatment. There are considerable amounts of research and publications that are able to well demonstrate the unreliability of relative density as an acceptance criterion. Relative density has no real influence on the soil's performance, its range of application does not span across all soil types, and it is subject to large inherent errors that make its use a technical risk. Here, the reasons why the concept of relative density is unreliable and should not be used for a ground improvement acceptance criterion are presented and discussed